Does Exposure to General Anesthesia Increase Risk of ADHD for Children Before Age of Three? - Junjie Song (Frontiers Media S.A., 2021)
Objective: The objective of the study was to evaluate the relationship between frequency of exposure to general anesthesia before the age of 3 and subsequent risk of diagnosis for attention-deficit hyperactivity disorder (ADHD).Method: We searched PubMed, Embase, Web of Science, and Cochrane Library database for eligible inclusion in the meta-analysis. The indicated outcomes were extracted from the included studies, and the combined effects were calculated using the RevMan software 5.3.Results: Compared with no exposure to general anesthesia, single exposure to general anesthesia did not increase the risk of ADHD for children before the age of 3 [hazard ratio (HR): 1.14, 95%; confidence intervals (CI): 0.97–1.35; p = 0.11; I2 = 0%], while multiple exposures to general anesthesia did increase the risk of ADHD (HR: 1.83; 95% CIs: 1.00–3.32; p = 0.05; I2 = 81%).Conclusion: Multiple, but not single, exposures to general anesthesia in children before age of 3 increased the risk of ADHD.